Race, Homeownership and Wealth - Thomas M. Shapiro (Washington University Journal of Law & Policy, 2006)
Closing the racial wealth gap must be at the forefront of the civil rights agenda in the twenty-first century. This Essay examines homeownership as a main policy strategy to move toward this goal. The Essay opens by restating the crucial importance of closing the racial wealth gap, and offers an early assessment of this agenda. Next, the Essay argues that homeownership is an appropriate strategy to attack the racial wealth gap. Finally, the Essay examines the various promises and many potential pitfalls and challenges facing minority homeownership.
Keywords: African Americans; Blacks; Home ownership; Housing discrimination; Race discrimination; Wage gap; United States; Race; Wealth